Export and its support tools in Ukraine - Molnar, Nikoletta; Berezovska, Olga (My University, 2015)
A powerful export potential of Ukraine is analyzed. The advantages for export producers and economy of the country are revealed.
Keywords: export potential; export producers; export; виробники експорту; експорт; експортний потенціал; экспортный потенциал; производители экспорта; экспорт; кафедра ділової іноземної мови та міжнародної комунікації